Clinical nursing skills & techniques - Perry, Anne Griffin; Potter, Patricia Ann; Ostendorf, Wendy (St. Louis Missouri Elsevier, 2018)
Clinical Nursing Skills & Techniques offers clear and comprehensive coverage of over 200 basic, intermediate and advanced skills. Features nearly 1,000 full-color photographs and drawings, a nursing process framework, step-by-step instructions with rationales, and a focus on critical thinking and evidence-based practice. This edition also includes new coverage of patient-centered care and safety guidelines, an enhanced emphasis on QSEN core competencies, and an expanded clinical focus with specialized Clinical Debriefs, Teach-Back, and sample documentation throughout.
Keywords: Nursing; Nursing Care; Clinical Medicine; Evidence-Based Nursing; Nursing